(untitled) (Journal of Parents and Teachers, 2014)
Parents are the first educators of their children; this task will be shared in the future with other agents, such as educators. For this reason, it is imperative to create a good relationship between parents and the chosen school. According to the Constitution, parents have the right to participate in schools, collaborating with their children’s educators and even contributing to the management of the school. The educational institutions must favor, encourage and propitiate the participation of the family in all the areas that the law recognizes. In addition, centers should provide basic information and appropriate training to parents.